2017
DOI: 10.1016/j.memsci.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A new zeolitic hydroxymethylimidazolate material and its use in mixed matrix membranes based on 6FDA-DAM for gas separation

Abstract: The new ZIF named UZAR-S13 is formed by Zn 2+ and 4(5)-(hydroxymethyl)imidazolate. UZAR-S13 has two distinct phases according to SEM and XRD: amorphous spheres and sheet crystals. UZAR-S13 and byproducts, with no N 2 adsorption, rendered a notable CO 2 uptake (up to 3.8 mmol g-1 at 30 bar and 0 °C), approaching values of known ZIFs. The most promising materials were included as fillers in mixed matrix membranes based on copolyimide 6FDA-DAM to study the separation of CO 2 /CH 4 , CO 2 /N 2 , H 2 /CO 2 and H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…He as sweep gas at 1 cm 3 (STP)•min −1 was used and controlled using an additional mass flow controller. The permeation module is as described elsewhere [12]. The permeate compositions were analyzed online by an Agilent 3000A micro-GC equipped with a thermal conductivity detector.…”
Section: Gas Separation Performancementioning
confidence: 99%
“…He as sweep gas at 1 cm 3 (STP)•min −1 was used and controlled using an additional mass flow controller. The permeation module is as described elsewhere [12]. The permeate compositions were analyzed online by an Agilent 3000A micro-GC equipped with a thermal conductivity detector.…”
Section: Gas Separation Performancementioning
confidence: 99%
“…A variety of fillers including silica, zeolites, graphene oxide, carbon nanotube, nanoparticles, frameworks, and porous organic cages as well as covalent and metal–organic frameworks (COFs and MOFs) have already been tested. MOFs are excellent fillers due to their crystalline characters with well-defined chemistry, large surface areas, and controlled porosity. MOF chemistry also facilitates interfacial interaction with polymeric matrix and enhances resistance to plasticization, thus further improving the membrane performance. , Particularly, zirconium­(IV)–carboxylate MOFs (Zr-MOFs) have emerged in membrane technologies as the inorganic fillers of choice due to their exceptional chemical and thermal stability arising from the strong coordination bonds between the “hard-acid”–“hard-base” interactions between the Zr­(IV) atoms and carboxylate oxygens. The typical Zr-MOFs include UiO-66 and UiO-66-NH 2 that exhibit a good performance in CO 2 separation. ,, …”
Section: Introductionmentioning
confidence: 99%
“…For the porous fillers, the effects are primarily related to their structures and pore sizes, acting as a molecular sieve and separating the permeating gases according to their molecular shapes and kinetic sizes. Due to their precise apertures, MMMs with porous fillers usually exhibit high permeability and selectivity, i.e., the addition of Zr-based MOFs [29,86] and Zn-based MOFs [87,88] in 6FDA-based polyimides. For ease of understanding, a schematic illustration is presented in Figure 5Error!…”
Section: Role Of Fillers In Mmms For Gas Separationmentioning
confidence: 99%
“…Zeolitic imidazolate frameworks (ZIFs), a subclass of MOFs, are constructed of imidazolate (im) anionic organic ligands tetrahedrally coordinated by transition metals (M). ZIF-8, the best-known ZIF, comprised of [Zn(mim)2]•nG (mim = 2-methylimidazole, G = guest) crystallites (see Figure 8(a)), possess the zeolite analogous O-Si-O sodalite topology (SOD), resulting in the M-im-M bridges being at 145° [123], thus giving them highly stable permanent pore apertures and excellent gas separation improvement in many polymer membranes [86,87,124]. Bushell et al [71] reported the use of nano-ZIF-8 (ABET = 1,300 m 2 ·g -1 ; average size of ~50 nm) into PIM-1.…”
Section: Zeolitic Imidazolate Framework (Zifs)mentioning
confidence: 99%